Cuticular wax coverage and its transpiration barrier properties in Quercus coccifera L. leaves: does the environment matter?. (14th November 2019) - Bueno, Amauri; Sancho-Knapik, Domingo; Gil-Pelegrín, Eustaquio; Leide, Jana; Peguero-Pina, José Javier; Burghardt, Markus; Riederer, Markus
Abstract: Plants prevent uncontrolled water loss by synthesizing, depositing and maintaining a hydrophobic layer over their primary aerial organs—the plant cuticle. Quercus coccifera L. can plastically respond to environmental conditions at the cuticular level. When exposed to hot summer conditions with high vapour-pressure deficit (VPD) and intense solar radiation (Mediterranean atmospheric conditions; MED), this plant species accumulates leaf cuticular waxes even over the stomata, thereby decreasing transpirational water loss. However, under mild summer conditions with moderate VPD and regular solar radiation (temperate atmospheric conditions; TEM), this effect is sharply reduced. Despite the ecophysiological importance of the cuticular waxes of Q. coccifera, the wax composition and its contribution to avoiding uncontrolled dehydration remain unknown. Thus, we determined several leaf traits for plants exposed to both MED and TEM conditions. Further, we qualitatively and quantitatively investigated the cuticular lipid composition by gas chromatography. Finally, we measured the minimum leaf conductance (gmin ) as an indicator of the efficacy of the cuticular transpiration barrier. The MED leaves were smaller, stiffer and contained a higher load of cuticular lipids than TEM leaves. The amounts of leaf cutin and cuticular waxes of MED plants were 1.4 times and 2.6 times higher than that found for TEM plants, respectively. In detail, MED plants produced higher amounts of all compound classes of cuticular waxes, except for the equivalence of alkanoic acids. Although MED leaves contained higher cutin and cuticular wax loads, the gmin was not different between the two habitats. Our findings suggest that the qualitative accumulation of equivalent cuticular waxes might compensate for the higher wax amount of MED plants, thereby contributing equally to the efficacy of the cuticular transpirational barrier of Q. coccifera . In conclusion, we showed that atmospheric conditions profoundly affect the cuticular lipid composition of Q. coccifera leaves, but do not alter its transpiration barrier properties.